Fish life-history traits predict abundance-occupancy patterns in artificial lakes - Miranda, L. E. (Frontiers in Freshwater Science, 2023)
Life-history traits of a species have been postulated as a factor in abundance and occupancy patterns. Understanding how traits contribute to the ubiquity and rarity of taxa can facilitate the development of effective conservation policy by establishing a connection between species requirements and resource. I evaluated fish assemblages in artificial lakes for evidence of the abundance-occupancy patterns reported in natural environments and, if evident, to explore if observed patterns of abundance and occupancy could be attributed to species traits. Consistent with reports for many other taxonomic groups in natural environments, there was a positive association amidst 114 fish species between abundance and occupancy in artificial lakes (R 2 = 0.78). This result indicates that the fish assemblages that develop in these anthropized environments follow the fundamental abundance-occupancy patterns uncovered in natural environments, despite assemblages having been disfigured by the dramatic rearrangement of habitats brought by impoundment. Moreover, a redundancy analysis focusing mostly on reproductive and habitat traits adequately predicted abundance-occupancy patterns of fish assemblages in artificial lakes (R 2 = 0.69). Species abundance-occupancy is influenced by the interplay between life-history traits and habitat availability, even in artificial lakes, and by extension, possibly other artificial ecosystems.